Longitudinal evaluation of bond strength to enamel of dental adhesive systems associated with Nd:YAG laser - Barcellos, D. C. [UNESP]; Batista, G. R. [UNESP]; Pucci, C. R. [UNESP]; Persici, E. S.; Borges, A. B. [UNESP]; Torres, C. R. G. [UNESP]; Fonseca, B. M. [UNESP]; Goncalves, S. E. P. [UNESP] (Operative Dentistry Inc, 2015)
Objectives: This study evaluated the durability of bond strength to enamel using total-etch (Single Bond/SB) and self-etch (Clearfil SE Bond/CSEB) adhesives associated with neody-mium: yttrium-aluminu- garnet (Nd:YAG) laser irradiation through the uncured adhesives.Methods: Bovine incisors were worn to expose an area of enamel and were divided into four groups: group 1 (control) SB + polymerization; group 2 (control) CSEB + polymerization; group 3 (laser) - B + Nd:YAG laser (174.16 J/cm(2)) + polymerization; and group 4 (laser) CSEB + Nd:YAG (174.16 J/cm(2)) + polymerization. Blocks of composite were fabricated and stored for 24 hours or 12 months, sectioned into beams, and submitted to microtensile tests. Results were analyzed by three-way analysis of variance (ANOVA) (adhesive, technique, and storage time) and Tukey tests.Results: ANOVA revealed significant differences for adhesive 3 technique and technique 3 storage time (p<0.05). The mean values (MPa) for interaction adhesive x technique (standard deviation) were as follows: SB/control = 35.78 (6.04)a; SB/laser = 26.40 (7.25)b, CSEB/control = 26.32 (5.71)b, CSEB/laser = 23.90 (7.49)b. For interaction technique x storage time the mean values were as follows: control/24 hours = 32.58 (6.49)a; control/12 months = 29.52 (8.38)a; laser/24 hours = 29.37 (5.71)a; laser/12 months = 20.92 (6.5)b. Groups with the same letters showed no statistically significant differences.Conclusion: Scanning electron microscope analysis showed evident areas of micromorphological alterations in lased samples after 12 months of water storage. Nd: YAG laser irradiation of enamel through unpolymerized totaletch adhesive significantly reduced bond strength compared with the control. Bond strength decreased when enamel samples irradiated with Nd: YAG laser through unpolymerized adhesives were stored in water for 12 months.